The Impact of Nurse Delegation Regulations on the Provision of Home Care Services: A Four-State Case Study. (February 2021) - Dudley, Nancy; Miller, Jacqueline; Breslin, Mary Lou; Chapman, Susan A.; Spetz, Joanne
The objective of this study was to explore how home care workers and the agencies that employ them interact with their state's nurse practice act in the provision of care. Using a qualitative case study approach, we selected four states with varying levels of restrictiveness in their nurse delegation regulations. We conducted interviews ( N = 45) with state leaders, agency leaders, and home care workers to learn how these policies affect the home care workforce's ability to perform care tasks for their clients in order to allow clients to remain in their own homes. We found that increased training and input from registered nurses is needed to identify appropriate health maintenance tasks to delegate to home care workers and support development of training strategies. The federal government could support the development of evidence-based guidelines for training and competency testing as well as for appropriate delegation of health maintenance tasks.